Carbon concentration and oxygen availability affect lipid and carotenoid production by carob pulp syrup‐grown Rhodosporidium toruloides NCYC 921. Issue 8 (25th August 2015) - Parreira, Teresa Margarida; Freitas, Claudia; Reis, Alberto; Roseiro, José; da Silva, Teresa Lopes
Abstract : The simultaneous effect of oxygen availability and carbon source concentration on yeast lipid and carotenoid production has never been studied before. In this work, a Doehlert distribution design was used to study the simultaneous effect of carbon concentration and oxygen availability on Rhodosporidium toruloides NCYC 921 carotenoid and lipid production. A cheap industrial byproduct was used as carbon source (carob pulp syrup). A total sugar concentration of 106.3 g/L and a medium volume of 0.120 L induced the highest total carotenoid and total fatty acid productivities (4.60 μg/Lh and 0.029 g/Lh, respectively). Flow cytometry was used to assess yeast stress response under different cultivation conditions. The highest proportion of cells with permeabilised membrane (>20%) was induced when the cultivations were carried out at the highest sugar concentration studied (130.0 g/L) or when the culture reached the minimum final medium pH (4.60). The results showed that the total sugar concentration had a positive influence on the yeast biomass and carotenoid content, while the oxygen availability had little influence on the biomass concentration, but had a slight positive influence on the carotenoid content. Regarding the fatty acids, the two factors had a negative impact on the synthesis of these compounds.